Turn Your AART into a HIT Using a Complete Range of Aesthetic Injectables: Methodology for Combining Products to Maximise Patient Outcomes - Nikolis A; Avelar LET; Haddad A; Lam SCK; Metelitsa A; Prather HB; Rosengaus F; Enright KM; Lazarova DO; Prygoya I; Iachetti F (Dove Medical Press, 2024)
Andreas Nikolis,1,2 Luiz Eduardo Toledo Avelar,3 Alessandra Haddad,4 Stephanie Chuk Kwan Lam,5 Andrei Metelitsa,6 Heidi B Prather,7 Frank Rosengaus,8 Kaitlyn M Enright,1 Desislava Ognyanova Lazarova,9 Inna Prygoya,10 Fabio Iachetti10 1Clinical Research Unit, Erevna Innovations Inc, Westmount, Quebec, Canada; 2Department of Plastic Surgery, McGill University, Montreal, Quebec, Canada; 3Clinica Domani Luiz Avelar, Belo Horizonte, Minas Gerais, Brazil; 4Federal University of São Paulo and Hospital Israelita Albert Einstein, São Paulo, São Paulo, Brazil; 5Central Health Medical Practice, Hong Kong, People's Republic of China; 6Department of Dermatology, University of Calgary, Alberta, Canada; 7Westlake Dermatology, Austin, TX, USA; 8Dr. Rosengaus Clinic, Mexico City, Mexico; 9Galderma SA, Lausanne, Vaud, Switzerland; 10Galderma, Uppsala, SwedenCorrespondence: Andreas Nikolis, Email research@vicpark.comPurpose: Optimizing outcomes of aesthetic treatments with injectable products usually requires a consideration of the entire face to ensure balance, along with combination treatments that align with the patient's goals. To help injectors, a method of assessing the patient and developing an individualized, holistic treatment plan was developed. This methodology is termed Assessment, Anatomy, Range, and Treatment (AART™) and Holistic Individualized Treatments (HITs™). This article aims to describe and evaluate the novel and systematic AART-HIT™ methodology.Methods: The AART-HIT™ methodology, including its associated diagnostic tool the Facial Assessment Scale (FAS™), were developed to aid injectors in completing a patient assessment in which the entire face is evaluated, the relevant anatomy is considered, the science behind the available range of products is understood, and the treatment plan is individualised for the patient. Specifically, the HITs™ are methodologic tools for practitioners to perform a standardized, full facial assessment and to create an individualized treatment approach to holistically address a patient's aesthetic concerns. The use of this methodology in clinical practice was assessed via a survey, deployed to twenty-eight clinicians.Results: Over 85% of participants agreed that the AART-HIT™ methodology was adequate for their needs. Additionally, 100% of participants agreed that the temporal sequencing of HITs™ and the FAS™ diagnostic tool was useful in clinical practice. Furthermore, over 70% of participants agreed that the anatomical locations identified in each HIT™ were sufficient, while over 80% responded that the HITs™ adequately represented the range of products. Finally, over 85% of participants agreed that the HITs™ covered different ethnic skin types and various patient ages and, over 80% of participants responded that they would not add additional elements to any of the 5 HITs™.Conclusion: The AART-HIT™ methodology, including the FAS™ were comprehensive enough for clinical use in providing a personalised treatment plan for individual patients.Keywords: fillers, biostimulators, neuromodulators, hyaluronic acid, education, treatment techniques